2012
DOI: 10.4049/jimmunol.1103183
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Dendritic Cell Activation and Antigen Exposure Is Required for the Induction of Th1/Th17 Responses

Abstract: The dendritic cell (DC) targeting/activation patterns required to elicit Th1/Th17 responses remain undefined. One postulated requirement was that of a physical linkage between Ags and immunomodulators. Accordingly, the separate same-site administration of Ag85B–ESAT-6 (hybrid-1 protein; H1), a mycobacterial fusion Ag, and the CAF01 liposome-based adjuvant induced similar Ab and weak Th2 responses as those of coformulated H1/CAF01 but failed to elicit Th1/Th17 responses. Yet, this separate same-site injection g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 64 publications
4
63
1
1
Order By: Relevance
“…The rapid activation of DCs at a stage when the Ag was most readily available to be endocytosed (i.e., soon after immunization) may be an additional key factor in establishing a strong T cell response. This is suggested by Kamath et al (40) who recently demonstrated that, in the converse situation, the early recruitment of nonactivated Ag-loaded APCs with in the dLN may be detrimental for Th1 responses. Given that high adaptive responses were achieved even when Ag was injected hours after AS01, our study shows that high adaptive responses can be associated with a rapid induction of inflammation and APC activation and may not require a physical association between adjuvant and Ag.…”
Section: Discussionmentioning
confidence: 79%
“…The rapid activation of DCs at a stage when the Ag was most readily available to be endocytosed (i.e., soon after immunization) may be an additional key factor in establishing a strong T cell response. This is suggested by Kamath et al (40) who recently demonstrated that, in the converse situation, the early recruitment of nonactivated Ag-loaded APCs with in the dLN may be detrimental for Th1 responses. Given that high adaptive responses were achieved even when Ag was injected hours after AS01, our study shows that high adaptive responses can be associated with a rapid induction of inflammation and APC activation and may not require a physical association between adjuvant and Ag.…”
Section: Discussionmentioning
confidence: 79%
“…Because no increase in activation-induced cell death or viability after stimulation was observed, it could be speculated that higher vaccine doses led to free Ag not bound by liposome-based CAF. Free Ag drains faster to the draining lymph node and is processed and presented by nonactivated DCs, in turn inducing tolerized or even inhibitory regulatory Ag-specific T cells (44). In fact, the 50-nmol PCLUS6.1-P18 vaccine dose equals ∼1.2 mg/ml, and for a similar liposomal adjuvant (CAF01), concentrations .…”
Section: Discussionmentioning
confidence: 99%
“…A particulate carrier loaded with the vaccine antigen and adjuvants was incorporated into the formulation in order to mimic the presence of pathogens and to facilitate synchronous uptake of the vaccine components by APCs (7,8). PLGA-NP were chosen due to their biocompatibility, stability, and versatility.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, particulate carriers may facilitate the synchronous presentation of vaccine antigens and adjuvants to dendritic cells, decreasing the potential for the development of tolerogenic immune response (7). Poly lactic-co-glycolic acid nanoparticles (PLGA-NP) have been extensively studied for vaccine delivery and have been reported to target dendritic cells naturally through phagocytosis with efficient delivery of the vaccine components (8).…”
Section: Introductionmentioning
confidence: 99%